Selections from cultural writings - Antonio, Gramsci. 1891-1937; Forgacs, David . 1952-; Nowell-Smith, Geoffrey, 1939- (Cambridge, Mass. : Harvard University Press, 1985)
Although Antonio Gramsci died as Benito Mussolini's prisoner, leaving only newspaper articles and fragmentary notes, he is now seen as the most significant Marxist thinker since Lenin. This volume is
Includes index.
Keywords: Italian literature -- History and criticism; Italy -- Civilization